Pemberantasan Dan Penanggulangan Kejahatan Narkotika Oleh Satuan Reserse Narkoba Polres Pohuwato - Adriani A.L Gula; Moh. R.U. Puluhulawa; Apripari Apripari (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
One of the problems facing Indonesia is the increasing drug propaganda. Drugs are a serious threat to society, health and state security. Drug use can cause physical, mental and social damage to individuals and have a negative impact on families and society at large. The Indonesian government has taken various steps to overcome the drug problem. One of them is the enactment of strict laws related to drug propaganda.Pohuwato Regency, as the entry point to Gorontalo Province, is rife with cases of narcotics and illegal drugs, both by land route and distributed through dealers outside the area and local dealers. Users are also targeted at various groups, both upper middle class and lower middle class. The difficulty in uncovering cases can be due to the large area, modus operandi and advances in the field of communications, so that more progressive steps are needed in uncovering narcotics crime cases.